2019
DOI: 10.9734/ajraf/2018/v2i430022
|View full text |Cite
|
Sign up to set email alerts
|

Community Poultry Project for Conserving the Wildlife Species in Magombera Forest, Tanzania

Abstract: Aims:Poaching of wildlife is a major challenge in their conservation, including endemic ones like Procolobus gordonorum Matschie. Local communities in Udzungwa and Magombera poach for subsistence and small scale commerce. The Community poultry project adjacent to Magombera forest contributed towards enhancing the conservation of wildlife species through providing community with poultry as an alternative livelihood where meat and income can be generated in legal and convenient methods. Place and Duration of Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Tanzania is among the countries which make the east African community together with Kenya and have a more-less similar ecological nature. A study in Tanzania showed that the major challenges in chicken production were diseases, the lack market for chickens’ products, the rearing system, predators, and parasites ( Ngongolo et al., 2019 ). More studies need to be done in Tanzania particularly in Dodoma to understand the challenges facing chicken production.…”
Section: Introductionmentioning
confidence: 99%
“…Tanzania is among the countries which make the east African community together with Kenya and have a more-less similar ecological nature. A study in Tanzania showed that the major challenges in chicken production were diseases, the lack market for chickens’ products, the rearing system, predators, and parasites ( Ngongolo et al., 2019 ). More studies need to be done in Tanzania particularly in Dodoma to understand the challenges facing chicken production.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken production in many parts of rural and urban areas in African countries has contributed significantly as sources of protein, food security, employment, and income in resource-constrained communities ( Kabir et al., 2015 ; Ngongolo et al., 2019 ). A study by Kryger et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies elsewhere have shown various challenges including markets, diseases, and predation that can affect productivity of chicken. For instance, a study by Ngongolo et al. (2019) reported predation from wildlife, diseases, and markets are among the few challenges in chicken production.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found related trends to these findings. For instance, a study by Kalantan et al (1991) revealed that the susceptibility of chickens to Clinostomum complanatum was associated with age, sex, and breed while sex, age, and herd size were observed to be risk factors for trypanosome infection in Maasai Steppe cattle in Tanzania ( Ngongolo et al, 2019 ). Control interventions such as treatment and prophylaxis against chicken diseases helped lower the mortality rate of chickens.…”
Section: Discussionmentioning
confidence: 99%